An mRNA mix redirects dendritic cells towards an antiviral program, inducing anticancer cytotoxic stem cell and central memory CD8+ T cells - de Mey, Wout; Locy, Hanne; De Ridder, Kirsten; De Schrijver, Phaedra; Autaers, Dorien; Lakdimi, Asma; Esprit, Arthur; Franceschini, Lorenzo; Thielemans, Kris; Verdonck, Magali; Breckpot, Karine (Frontiers in Immunology, 2023)
Dendritic cell (DC)-maturation stimuli determine the potency of these antigen-presenting cells and, therefore, the quality of the T-cell response. Here we describe that the maturation of DCs via TriMix mRNA, encoding CD40 ligand, a constitutively active variant of toll-like receptor 4 and the co-stimulatory molecule CD70, enables an antibacterial transcriptional program. Besides, we further show that the DCs are redirected into an antiviral transcriptional program when CD70 mRNA in TriMix is replaced with mRNA encoding interferon-gamma and a decoy interleukin-10 receptor alpha, forming a four-component mixture referred to as TetraMix mRNA. The resulting TetraMixDCs show a high potential to induce tumor antigen-specific T cells within bulk CD8+ T cells. Tumor-specific antigens (TSAs) are emerging and attractive targets for cancer immunotherapy. As T-cell receptors recognizing TSAs are predominantly present on naive CD8+ T cells (TN), we further addressed the activation of tumor antigen-specific T cells when CD8+ TN cells are stimulated by TriMixDCs or TetraMixDCs. In both conditions, the stimulation resulted in a shift from CD8+ TN cells into tumor antigen-specific stem cell-like memory, effector memory and central memory T cells with cytotoxic capacity. These findings suggest that TetraMix mRNA, and the antiviral maturation program it induces in DCs, triggers an antitumor immune reaction in cancer patients.